Evaluasi Penerapan Pelayanan Farmasi Klinik di Apotek Daerah Sleman: Evaluasi Penerapan Pelayanan Farmasi Klinik di Apotek Daerah Sleman - Aji Tetuko; Melia Eka Rosita (Jurnal Pelayanan Kefarmasian dan Sains, 2023)
Background : Clinical pharmacy services at the pharmacy are part of pharmaceutical services that are direct and responsible to patients. Apoteker must practice in accordance with applicable service standards. Objective : The purpose of this study is to determine the application of clinical pharmacy services in the Sleman regional pharmacy based on Permenkes Number 73 of 2016. Method : This research was conducted descriptively with a cross-sectional method and data collection directly. Data collection was carried out using primary data, namely checklist data adapted from Permenkes Number 73 of 2016 concerning pharmacy service standards in pharmacies. Result : The results show that pharmaceutical services at Pharmacy A and Pharmacy B in the Sleman area of Yogyakarta have not fully implemented pharmaceutical service standards based on the Regulation of the Minister of Health no. 73 of 2016. Pharmaceutical services at the Drug Information Service (PIO) are not carried out entirely, at Pharmacy A does not provide information about special formulas, while in Pharmacy B does not provide information about special formulas and pharmacokinetics. Conclusion : In addition to Drug Information Services (PIO) that are not fully carried out, Pharmacy A and Pharmacy B have carried out pharmaceutical service standards in accordance with applicable regulations. Keywords : clinical pharmacy services, clinical pharmacy pharmacy, Permenkes number 73 of 2016, pharmacy.